IMPLEMENTASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI LINGKUNGAN PEMERINTAH KOTA PALEMBANG - HASNI YUSRIANTI; RIKA HENDA SAFITRI (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aims to evaluate implementation of Government Performance Accountability System (SAKIP) in Government of Palembang City. It is a qualitative research using primary and secondary data. Data obtained by structured interviews with the responsible parties at Palembang Government and by using LAKIP documentation of Regional Secretariat of Palembang City. The analysis was in two steps that are Evaluation of SAKIP implementation and Analysis of interviews results includes data reduction, data categorization, data synthesis, and drawing conclusions. The results showed that overall the achievement level of SAKIP implementation of SKPD is mostly classified in less good so it requires assistance in LAKIP preparation. The obstacles encountered which are; weak control and monitoring functions, limited budget allocations, lack of management commitment, lack of quality and quantity of human resources, lack of coordination.